(untitled) (Clinics, 2014)
OBJECTIVE: To determine the effects of a formal auditory training program on the behavioral, electrophysiological and subjective aspects of auditory function in individuals with bilateral high-frequency hearing loss. METHOD: A prospective study of seven individuals aged 46 to 57 years with symmetric, moderate high-frequency hearing loss ranging from 3 to 8 kHz was conducted. Evaluations of auditory processing (sound location, verbal and non-verbal sequential memory tests, the speech-in-noise test, the staggered spondaic word test, synthetic sentence identification with competitive ipsilateral and contralateral competitive messages, random gap detection and the standard duration test), auditory brainstem response and long-latency potentials and the administration of the Abbreviated Profile of Hearing Aid Benefit questionnaire were performed in a sound booth before and immediately after formal auditory training. RESULTS: All of the participants demonstrated abnormal pre-training long-latency characteristics (abnormal latency or absence of the P3 component) and these abnormal characteristics were maintained in six of the seven individuals at the post-training evaluation. No significant differences were found between ears in the quantitative analysis of auditory brainstem responses or long-latency potentials. However, the subjects demonstrated improvements on all behavioral tests. For the questionnaire, the difference on the background noise subscale achieved statistical significance. CONCLUSION: Auditory training in adults with high-frequency hearing loss led to improvements in figure-background hearing skills for verbal sounds, temporal ordination and resolution, and communication in noisy environments. Electrophysiological changes were also observed because, after the training, some long latency components that were absent pre-training were observed during the re-evaluation.